SEA presidential address: Group connectivity and cooperation - Amparo Urbano (SERIEs - Journal of the Spanish Economic Association, 2011)
A model-free methodology is used for the first time to estimate a daily volatility index (VIBEX-NEW) for the Spanish financial market.We use a public data set of daily option prices to compute this index and showthat daily changes in VIBEXNEW display a negative, tight contemporaneous relationship with IBEX daily returns, contrary to other common volatility indicators, as an implied volatility indicator or a GARCH(1,1) conditional volatility model. This relationship is approximately symmetric to the sign on VIBEX-NEW changes and asymmetric to the IBEX-35 returns sign, which make it clearly a suitable volatility index for the Spanish stock market. We also examine the relationship between current VIBEX-NEW and future IBEX-35 volatility. Our results suggest that VIBEX-NEW can be used to produce IBEX-35 volatility forecasts at least as good as historical and conditional volatility measures. A feasible volatility correction methodology is proposed to achieve it.
Keywords: C53; G13; G15; 330; model-based volatility index; model-free volatility index; risk; leverage effect; forecasting volatility; Gefangenendilemma; Evolutionäre Spieltheorie